С.ЖУМАҒУЛОВ ШЫҒАРМАЛАРЫ ТИЛИНДЕ СЕСЛИК ТӘКИРАРЛЫ ФРАЗЕОЛОГИЗМЛЕР - Юсупова, Б.Т. (FAN va JAMIYAT, 2021)
The article analyzes the artistic role of phraseologisms in the language of fiction, the features of their use, the possibilities of creating artistic imagery are analyzed in the basis of the language of humorous stories of the writer S. Zhumagulov, the writer's own methods of using them, ways of using them in educational relation and personal skill are determined.